PENERAPAN AZAS OPORTUNITAS BERHUBUNGAN DENGAN TUGAS DAN WEWENANG KEJAKSAAN DALAM SISTEM PERADILAN PIDANA (KAJIAN PERKARA TERHADAP TERDAKWA NOVEL BIN SALIM BASWEDAN) - Napitupulu, Tumpal (Faculty of Law, Tanjungpura University, 2018)
The public prosecutor is not required to prosecute a person committing an offense if at his discretion, if the person prosecuted can harm the public interest. No prosecution of a person committing a crime in the public interest, known as deponering whose authority resides with the Attorney General under Article 35 Sub-Article c of Law Number 16 Year 2004 regarding the Attorney of the Republic of Indonesia. In addition to the authority of deponering, the Attorney General is also authorized to stop prosecution under Article 144 paragraph (1) of Law Number 8 Year 1981 regarding Criminal Procedure Law which is manifested in the form of Prosecution Cessation Decree (SKP2). Starting from the authority to stop prosecution owned by the Attorney there are problems, namely: (1). When the Attorney's Office actually stop prosecuting a case in the criminal justice system and is it appropriate that the Attorney's Office issued SKP2 in case the case has been registered in the district court? (2). How to overcome the problems that arise against the issuance of SKP2 by the Attorney in case the case has been registered in the district court. The study is directed to the SKP2 case study in the Novel Baswedan case. Based on the results of the study can be concluded: (1). The Attorney's Office issued SKP2 in the Novel Baswedan case with insufficient consideration of the evidence and the case was closed by law and the Public Prosecutor's Office did not properly issue SKP2 when the case was registered in the district court. (2). to solve the problems arising from SKP2 issued by the Attorney there has been a pre-trial decision stating SKP2 is not valid, it must be resolved through the criminal justice system to obtain legal certainty.